2021
DOI: 10.3390/foods10020349
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earths as Authenticity Markers for the Discrimination of Greek and Turkish Pistachios Using Elemental Metabolomics and Chemometrics

Abstract: Pistachios are a nutritionally beneficial food source widely consumed all over the world. Pistachios exhibit high content of antioxidants, vitamins and other beneficial micronutrients, including nutrient elements and rare earth elements (REEs). Considering that the concentration of REEs depends on the climate and soil characteristics that vary among different geographical regions, REEs could constitute markers responsible for the geographical discrimination of this nut type. In this study, Greek pistachios wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Therefore, resistance evaluations are necessary across multiple years or locations (Buerstmayr et al, 2008; Yan et al, 2022). Cluster analysis is a method for dividing a group of objects into classes so that similar objects are in the same class (Gupta et al, 2022; Kalogiouri et al, 2021), while discriminant analysis is a multivariate analysis used to find the linear combination of features that distinguish two or more classes (Huberty, 1975; Stella, 2019). Combining cluster analysis with discriminant analysis helps to improve the accuracy of classification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, resistance evaluations are necessary across multiple years or locations (Buerstmayr et al, 2008; Yan et al, 2022). Cluster analysis is a method for dividing a group of objects into classes so that similar objects are in the same class (Gupta et al, 2022; Kalogiouri et al, 2021), while discriminant analysis is a multivariate analysis used to find the linear combination of features that distinguish two or more classes (Huberty, 1975; Stella, 2019). Combining cluster analysis with discriminant analysis helps to improve the accuracy of classification.…”
Section: Discussionmentioning
confidence: 99%
“…are well-known superfoods; they are an excellent source of protein, fiber, fats, vitamins, and minerals. Literature research showed an increasing interest in studying the elemental composition of nuts for geographical origin authentication [ 193 , 194 , 195 , 196 , 197 , 198 ] the last five years. The first attempt to classify hazelnuts according to their geographical origin was accomplished by Oddone et al [ 193 ], in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Chemometric analyses of nuts described in the literature are primarily related to data on the chromatographic fingerprint [ 61 ], interpretation of results obtained by Raman spectroscopy [ 62 ] or Fourier transform infrared spectroscopy [ 63 ], or a combination of chemometric and metabolomic techniques [ 64 ].…”
Section: Discussionmentioning
confidence: 99%